PATTERN OF SOCIAL CAPITAL IN EMPOWERMENT OF URBAN AND RURAL COMMUNITIES IN INDONESIA - Moh. Dulkiah (Ikatan Dosen Menulis, 2022)
This study departs from a problem in the application of social capital in community empowerment activities in urban and rural areas in Indonesia. This study aims to determine the application model that is applied in community empowerment in urban and rural areas. The method used in this research is in-depth interviews with facilitators and community members who are the subject of empowerment. This study finds that social capital can be built when individuals can trust others, so they can make responsible commitments to build mutually beneficial relationships. The exchange of information that is facilitated by social networks to interact ultimately contributes to creating trust between them. This belief is closely related to cultural roots, especially those related to applicable ethics and morals. Therefore, the degree of mutual trust in society cannot be separated from the cultural values ​​of the community concerned. Social families and belief groups can grow an economy where trust is correlated with economic growth. This study concludes that the application of social capital in urban and rural empowerment relies on the model of cooperation that is built, the use of networks and the development of positive values ​​in society.